2008
DOI: 10.1111/j.1471-4159.2008.05647.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic exposure to morphine on the rat blood–brain barrier: focus on the P‐glycoprotein

Abstract: Morphine is well tolerated but addictive, especially for heroin consumers, as heroin is rapidly metabolised to morphine in humans. The hypothesis that psychostimulant drugs, like morphine and/or its withdrawal may cause severe stress that could affect the properties of the blood-brain barrier (BBB) by modifying BBB constitutive markers has been poorly investigated. A recent study has shown that the integrity of the BBB of rats chronically given morphine is altered from 1 day after the last morphine dose, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 38 publications
2
52
1
1
Order By: Relevance
“…In rats chronically treated with morphine, in situ perfusion of sucrose did not allow its penetration into the BBB [15].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In rats chronically treated with morphine, in situ perfusion of sucrose did not allow its penetration into the BBB [15].…”
Section: Discussionmentioning
confidence: 93%
“…Data on the effects of chronic exposure to morphine are conflicting [14,15]. In rats chronically treated with morphine, in situ perfusion of sucrose did not allow its penetration into the BBB [15].…”
Section: Discussionmentioning
confidence: 99%
“…11,23 The aim of this new work was to know whether morphine itself or its subsequent precipitated withdrawal syndrome was responsible for P-gp and Bcrp upregulation in the rat BBB.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the relative mRNA expression of breast cancer resistance protein (BCRP/ABCG2) to MDR1/mdr1a/ABCB1 was higher in human brain microvessels than in rat brain microvessels. 6,7 However, mRNA expression levels do not necessarily correlate with protein expression levels. Indeed, it was reported that the protein expression of MDR1 and BCRP was downregulated by activation of estrogen receptor "-related pathways without any change of mRNA expression.…”
Section: Introductionmentioning
confidence: 99%